Transition to parenthood: The role of social interaction and endogenous networks - Belinda Aparicio Diaz; Thomas Fent; Alexia Prskawetz; Laura Bernardi (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2007)
Empirical studies indicate that the transition to parenthood is influenced by an individual's peer group. To study the mechanisms that create interdependencies across individuals' transition to parenthood and its timing we apply an agent-based simulation model. We build a one-sex model and provide agents with four different characteristics. Based on these characteristics, agents endogenously form their network. Network members then may influence the agents' transition to higher parity levels. Our numerical simulations indicate that accounting for social interactions can explain the shift of first-birth probabilities in Austria over the period 1984 to 2004. Moreover, we apply our model to forecast age-specific fertility rates up to 2021.
Keywords: 300; Transition to parenthood; changes in age specific fertility rates; agent-based model; social interaction; endogenous network; Soziale Beziehungen; Fertilität; Bevölkerungsentwicklung; Bevölkerungsprognose; Agentenbasierte Modellierung; Österreich